Maceral Characteristics and Vitrinite Reflectance Variation of The High Rank Coals, South Walker Creek, Bowen Basin, Australia - Asep K. Permana; C. R. Ward; L. W. Gurba (Geological Agency, 2013)
DOI: 10.17014/ijog.v8i2.156The Permian coals of the South Walker Creek area, with a vitrinite reflectance (Rvmax) of 1.7 to 1.95% (low-volatile bituminous to semi-anthracite), are one of the highest rank coals currently mined in the Bowen Basin for the pulverized coal injection (PCI) market. Studies of petrology of this coal seam have identified that the maceral composition of the coals are dominated by inertinite with lesser vitrinite, and only minor amounts of liptinite. Clay minerals, quartz, and carbonates can be seen under the optical microscope. The mineral matter occurs in association with vitrinite and inertinite macerals as syngenetic and epigenetic mineral phases. The irregular pattern of the vitrinite reflectance profile from the top to the bottom of the seam may represent a response in the organic matter to an uneven heat distribution from such hydrothermal influence. Examination of the maceral and vitrinite reflectance characteristics suggest that the mineralogical variation within the coal seam at South Walker Creek may have been controlled by various geological processes, including sediment input into the peat swamp during deposition, mineralogical changes associated with the rank advance process or metamorphism, and/or hydrothermal effects due to post depositional fluid migration through the coal seam.